Dynamic Changes of Peripheral NK Cells Predict Outcome in Patients with PD-L1 Positive Non-small-cell Lung Cancer Undergoing Immune Checkpoint Inhibitors as Second-line Therapy. (14th September 2022) - Nelli, Fabrizio; Panichi, Valentina; Fabbri, Agnese; Natoni, Federica; Giannarelli, Diana; Topini, Giuseppe; Virtuoso, Antonella; Giron Berrios, Julio Rodrigo; Marrucci, Eleonora; Pessina, Gloria; Silvestri, Maria Assunta; Ruggeri, Enzo Maria
Abstract: We evaluated immune cell frequencies in peripheral blood samples of 41 NSCLC patients before and after second-line therapy with anti-PD-1/PD-L1 agents. Changes in lymphocyte subsets and their correlation with clinical response, progression-free survival (PFS), and overall survival (OS) were analyzed. We observed an increase in median values of all lymphocyte subsets, being significant only for NK cells. A correlation was retrieved between higher post-treatment NK cell level and clinical benefit . On multivariate analysis, PD-L1 tumor proportion score ≥1% and higher post-treatment NK cell counts were predictive of longer PFS and OS. Co-presence of these factors was characterized by longer survival.